Upregulation of ferroptosis in glucocorticoids-induced posterior subcapsular cataracts - Yuhang Zhang; Wei Si; Yi Mao; Su Xu; Fuzhen Li; Jingjing Liu; Shanshan Du; Jingzhi Shao; Ying Qi; Xuyan Peng; Mengjiao Xue; Mingjun Jiang; et al. (Communications Biology)
Abstract The Glucocorticoid-induced posterior subcapsular cataracts (GIC) is a common complication of patients received glucocorticoid treatment in clinic. We find that dexamethasone (DEX) induces lens epithelial cells’ ferroptosis. DEX treatment increases intracellular ferroptosis signatures in lens epithelial cell line in vitro as well as in rat lens in vivo. The inhibition of ferroptosis by liproxstatin-1 reduces the incidence of DEX-induced rat GIC. Experimental evidence and expression profiling showed that DEX induces ferroptosis through upregulating tetraspanin CD82- controlled P53 expression. DEX-activated glucocorticoid receptors directly bind to the CD82 promoter, driving its transcriptional upregulation. CD82 expression is upregulated in the anterior capsular epithelium of GIC patients as well as in the DEX-treated rat lens and caused the cell death of anterior capsule. DEX treatment and Overexpression of CD82 in cells recapitulated ferroptotic signatures through P53 activation and GPX4/SLC7A11 suppression. Taken together, GIC is closely associated with the upregulation of CD82-P53-GPX4/SLC7A11 axis-mediated ferroptosis.